Who’s Afraid of White Class Migrants? On Denial, Discrediting, and Disdain (And Toward a Richer Conception of Diversity) - Pruitt, Lisa R. (Columbia Journal of Gender and Law, 2015)
This Article describes and theorizes the legal academy’s denial of both class disadvantage and class migration, with particular attention to how those phenomena are manifest in relation to white faculty. The Article observes that a general disdain for poor and working-class whites evolves into the denial and distancing of class migrants, those who move into the professoriate from lower socioeconomic stations (“SES”). Further, the academy simultaneously discredits and disciplines these class migrants when they run afoul of narrow norms regarding credentials, scholarship, and culture. The author employs storytelling as methodology, drawing on her own experiences as a white class migrant to illustrate some of these phenomena.